Computational vision and medical image processing recent trends - Tavares, João Manuel R. S.; Jorge, R. M. Natal; SpringerLink (Online service).; ECCOMAS thematic conference on Computational Vision and Medical Image processing (2009 Porto, Portugal). (Dordrecht Springer, 2011)
This book contains extended versions of papers presented at the international Conference VIPIMAGE 2009 ? ECCOMAS Thematic Conference on Computational Vision and Medical Image, that was held at Faculdade de Engenharia da Universidade do Porto, Portugal, from 14th to 16th of October 2009. This conference was the second ECCOMAS thematic conference on computational vision and medical image processing. It covered topics related to image processing and analysis, medical imaging and computational modelling and simulation, considering their multidisciplinary nature. The book collects the state-of-the-art research, methods and new trends on the subject of computational vision and medical image processing contributing to the development of these knowledge areas.
Preface -- Automatic Segmentation of the Optic Radiation Using DTI in Healthy Subjects and Patients with Glaucoma, by Ahmed El-Rafei, Tobias Engelhorn, Simone Waerntges, Arnd Doerfler, Joachim Hornegger, Georg Michelson -- Real Time Colour Based Player Tracking in Indoor Sports, by Catarina B. Santiago, Armando Sousa, Luís Paulo Reis, Maria Luísa Estriga -- Visualization of the Dynamics of the Female Pelvic Floor Reflex and Steady State Function, by Christos E. Constantinou, Qiyu Peng, Sadao Omata -- Population exposure and impact assessment - Benefits of modeling urban land use in very high spatial and thematic detail, by Christoph Aubrecht, Mario Köstl, Klaus Steinnocher -- Dynamic radiography imaging as a tool in the design and validation of a novel intelligent amputee socket, by George Papaioannou, Dimitrios Tsiokos, Goeran Fiedler, Christos Mitrogiannis, Ilya Adveev, Jake Wood, Ray McKinney -- A discrete level set approach for texture analysis of microscopic liver images, by D.Iacoviello -- Deformable and Functional Models, by Demetri Terzopolous -- Medical-GiD: From Medical Images to Simulations, 4D MRI Flow Analysis, by Eduardo Soudah, Julien Pennecot, Jorge S.Pérez, Maurizio Bordone, Eugenio Oñate -- KM and KHM clustering techniques for colour image quantization, by Mariusz Frackiewicz, Henryk Palus -- Caries Detection in Panoramic Dental X-ray Images, by João Oliveira, Hugo Proença -- Noisy Medical Image Edge Detection Algorithm Based on a Morphological Gradient Using Uninorms, by Manuel González-Hidalgo, Arnau Mir Torres, Daniel Ruiz Aguilera, Joan Torrens Sastre -- Leveraging Graphics Hardware for an Automatic Classification of Bone Tissue, by Manuel Jesús Martín-Requena, Manuel Ujaldón -- A novel template-based approach to the segmentation of the hippocampal region, by M. Aiello, P. Calvini, A. Chincarini, M. Esposito, G. Gemme, F. Isgrò, R. Prevete, M. Santoro, S. Squarcia -- Model-based Segmentation and Fusion of 3D Computed Tomography and 3D Ultrasound of the Eye for Radiotherapy Planning, by M. Bach Cuadra, S. Gorthi, F. I. Karahanoglu, B. Paquier, A. Pica, H.P. Do, A. Balmer, F. Munier, J.-Ph. Thiran -- Flow of a blood analogue solution through microfabricated hyperbolic contractions, by P. C. Sousa, I. S. Pinho, F. T. Pinho, M. S. N. Oliveira, M. A. Alves -- Molecular imaging of hypoxia using genetic biosensors, by Pablo Iglesias, J. A. Costoya -- Microscale flow dynamics of red blood cells in microchannels: an experimental and numerical analysis, by R. Lima, C.S. Fernandes, R. Dias, T. Ishikawa, Y. Imai, T. Yamaguchi -- Two Approaches for Automatic Nuclei Cell Counting in Low Resolution Fluorescence Images, by Thierry Brouard and Aurélie Chantôme and Alejandro Frangi.
"Selected from works presented at the second ECCOMAS thematic conference on Computational Vision and Medical Image processing (VIPimage 2009)".
Electronic reproduction.
Keywords: Computer vision -- Congresses; Computer vision in medicine -- Congresses; Diagnostic imaging -- Congresses; Electronic books